Discrimination of Cerrado vegetation cover in the state of Mato Grosso using MODIS images - Silva, Gustavo Bayma Siqueira da; Formaggio, Antonio Roberto; Shimabukuro, Yosio Edemir; Adami, Marcos; Sano, Edson Eyji (Pesquisa Agropecuaria Brasileira, 2011)
The objective of the present work was to evaluate the potential of the spectral linear mixture model (SLMM), applied to Moderate Resolution Imaging Spectroradiometer (MODIS) images, to discriminate natural and anthropic classes of vegetation in the portion of Mato Grosso state covered by Cerrado vegetation. The monitoring of the Cerrado biome is becoming very important due to its strong human disturbance, especially in the last four decades. In this context, the MODIS sensor appears as an option due to its high temporal resolution. However, considering its moderate spatial resolution, the decomposition of its spectral response is indicated. The SLMM appears to be a viable technique, since it permits estimating the percentage of components within the pixel. The data used in the temporal class profiles corresponded to the following fraction images derived from SLMM: vegetation, soil, and shade. Discrimination of natural and anthropogenic classes was determined through the Mahalanobis distance, presented by dendrograms. The fraction images allow time series analyses for spatial and temporal characterization of the classes. Soil and shade fraction images, in the dry season, present better results in the discrimination of selected classes. For the discrimination of classes with similar floristic composition, fraction images from the rainy season are indicated.